Coating technology on mortar surface for extending service life of on-site building construction - Jumrus Nidchamon; Thapinta Monwipa; Chaiwong Patcharaporn; Pantawan Arisara; Kumpika Tewasin; Thongpan Winai; Jhuntama Niwat; Kantarak Ekkapong; Sroila Wattikon; Rianyoi Rattiyakorn; Singjai Pisith; Thongsuwan Wiradej (Journal of the Serbian Chemical Society)
The superhydrophobic, self-cleaning and anti-corrosion surface was successfully coated on mortar using an effective one-step spray coating technique. A coating solution was prepared by mixing methyltrichlorosilane-modified SiO2/TiO2 nanoparticles at different ratios to enhance the superhydrophobicity and reduce water absorption of the mortar. The sample prepared using a SiO2/TiO2 with the ratio of 75/25 was found to be optimal, exhibiting a high water contact angle and low sliding angle, which resulted in a reduction of water absorption by more than 97.5 % and chloride ion penetration depth. Furthermore, the robustness of the superhydrophobic coating was analyzed against various tests including water drop impact, sand abrasion impact, tape peeling and sandpaper abrasion tests, each test was conducted with over 10000 drops, 300 g, 60 cycles and 5 cycles, respectively. Notably, the coating showed excellent water absorption reduction of 82.6 % after sandpaper abrasion for a length of 200 cm (20 cycles), even though the water contact angle was reduced to 118°. Thus, the fabrication of superhydrophobic mortar surface offers a novel, alternative approach that is simple, efficient, cost-effective and provides multifunction protection surface to increase the service life of on-site building construction with enhanced mechanical durability and anti-corrosion properties.